2014
DOI: 10.1016/j.ultsonch.2014.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of ultrasound-assisted extraction of phenolic compounds from grape marc: Influence of acoustic energy density and temperature

Abstract: The effects of acoustic energy density (6.8-47.4 W/L) and temperature (20-50 °C) on the extraction yields of total phenolics and tartaric esters during ultrasound-assisted extraction from grape marc were investigated in this study. The ultrasound treatment was performed in a 25-kHz ultrasound bath system and the 50% aqueous ethanol was used as the solvent. The initial extraction rate and final extraction yield increased with the increase of acoustic energy density and temperature. The two site kinetic model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 53 publications
9
102
0
5
Order By: Relevance
“…However, it is noteworthy that with an extraction time of 30 min, their values decreased and then re-increased. In effect, Tao et al [26] found that in the first 10-20 min of extraction the dissolution of the soluble components on the surfaces of the matrix occurs and it is at this stage that up to 90% of the recovery of the total content of the phenolic compounds can be achieved, thus indicating a considerable rapid extraction rate. Probably, the exposure of an ultrasonic irradiation of 30 min caused negative effects like oxidation, degradation, and/or polymerization of the phenolic and flavonoid compounds [27,28,29].…”
Section: Optimization Of Uae Timementioning
confidence: 99%
“…However, it is noteworthy that with an extraction time of 30 min, their values decreased and then re-increased. In effect, Tao et al [26] found that in the first 10-20 min of extraction the dissolution of the soluble components on the surfaces of the matrix occurs and it is at this stage that up to 90% of the recovery of the total content of the phenolic compounds can be achieved, thus indicating a considerable rapid extraction rate. Probably, the exposure of an ultrasonic irradiation of 30 min caused negative effects like oxidation, degradation, and/or polymerization of the phenolic and flavonoid compounds [27,28,29].…”
Section: Optimization Of Uae Timementioning
confidence: 99%
“…The change in flavonoid concentration in the solid phase with respect to time and radial position during MAE can be described using Fick's second law as follows (Tao et al, 2014a):…”
Section: Estimation Of Effective Diffusion Coefficient Mass Transfermentioning
confidence: 99%
“…Also higher temperatures aid in desorption of the solutes from active sites within the plant matrix (Veggi et al, 2013). The solute transfer from the solid-to-liquid phase is affected by transport properties such as effective diffusion coefficient (Tao et al, 2014a). With the increase in temperature, the effective diffusion coefficient for MAE of flavonoids also increased (Table 6) due to higher thermal energy at elevated temperatures.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Based on Fick's second law, the mathematical expression that links Y TP and the effective diffusion of the solute (polyphenols) can be described as follows [12]:…”
Section: Kinetic Assaymentioning
confidence: 99%
“…ð Þ Þ against t, it can be observed that in some instances, the points are scattered along two intersecting straight lines, one with a relatively steep slope and another one with a shallow slope [12,13]. As the first line corresponds to the fast stage of extraction (washing), which can be considered as the non-limiting stage, in this study the D e coefficients were calculated by determining the slope of the slow stage of diffusion process, which might be more indicative regarding the effect of the extraction medium.…”
Section: Kinetic Assaymentioning
confidence: 99%